Peran welas diri terhadap pengungkapan kesulitan pada individu dewasa awal dari keluarga yang bercerai - Nathalie, Giftania Grace; Dicky Sugianto (Jurnal Psikologi Ulayat, 2024)
Emerging adults who experienced parental divorce may face interpersonal difficulties, which can manifest as reduced distress disclosure. This study examines the role of self-compassion in distress disclosure among emerging adults with a history of parental divorce. A simple linear regression analysis was conducted on data collected from a survey of 128 young adults who had experienced parental divorce prior to the age of 16. Results indicate that, at an overall level, self-compassion did not significantly predict distress disclosure among emerging adults who experienced parental divorce. However, additional analysis suggests that the overidentification component of self-compassion correlated positively with distress disclosure. The duration of parental divorce (the time that had passed since the divorce) was positively correlated with overall self-compassion and the mindfulness component of self compassion, while correlating negatively with the self-judgment component of self-compassion. Cultural differences may explain these findings, where individuals in individualistic cultures tends to disclose difficulties to others, while those in collectivits cultures may supress such experiences.